Perancangan Pengenalan Angka Dan Warna Pada Anak Usia Dini Menggunakan Adobe Flash CS6 - Putri Yani Tambunan (Jurnal Informatika, 2022)
The education given to early childhood is the basis of future knowledge and thought processes to teach toddlers about basic things such as recognizing numbers and colors that need determination and patience from teachers and parents. The basic concepts of numbers and colors are important to study because they learn the basics of math to solve problems. During this study, parents and teachers carried out numbers and colors at school with the help of tools such as reading books, reading cards and other teaching aids. With the media it takes activities from parents or teachers to attract children, sometimes even children get bored. Therefore, it is necessary that alternative media can be used as a medium for early childhood learning through alternative media used in the form of animation that is attractive, easy and not boring quickly. The Number and Color Recognition application as a learning medium to attract children's attention so that it is easy to learn through numbers and colors without the problem of time and place limits.